Pengaruh Financial Deepening Terhadap Pertumbuhan Ekonomi di Indonesia - Valendio Allent Putra; Muhammad Irfan (Universitas Negeri Padang, 2023)
The purpose of this study is to determine the effect of Fincial Deepening on Economic Growth in Indonesia. The independent variable in this study is Findepth or the ratio of total loans to Nominal GRDP (X1) and the dependent variable is Economic Growth (Y). In this study also used control variabel, Labor or labor Force Ratio to population (X2) and Govexp variable or Ratio of government expenditure to Nominal GRDP (X3). This research is a descriptive and associative study. The data analysis used in this research is secondary data, the kind of data is panel data from 33 provinces in Indonesia from 2010-2019, the data sourced from the Central Agency for Stastistik, Indonesian Banking Statistics and Website of the Ministry of Finance of the Republic of Indonesia. The data analysis used in this research is descriptive and inductive analysis. In the inductive analysis there are several test, namely (1) Chow Test; (2) Hausman Test; (3) Panel data regression estimation test (FEM); (4) classical assumption test; (5) T test and F test. Based on the research, the result of this study is: (1) Findepth has a positive and significant effect on economic growth; (2) Labor has positive and significant effect on economic growth; (3) Govexp has a positive and significant effect on economic growth.